If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X * X + 3x = 70 Multiply X * X X2 + 3x = 70 Solving X2 + 3x = 70 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3x' to each side of the equation. X2 + 3x + -3x = 70 + -3x Combine like terms: 3x + -3x = 0 X2 + 0 = 70 + -3x X2 = 70 + -3x Simplifying X2 = 70 + -3x Reorder the terms: -70 + X2 + 3x = 70 + -3x + -70 + 3x Reorder the terms: -70 + X2 + 3x = 70 + -70 + -3x + 3x Combine like terms: 70 + -70 = 0 -70 + X2 + 3x = 0 + -3x + 3x -70 + X2 + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 -70 + X2 + 3x = 0 The solution to this equation could not be determined.
| V=(16-2x)(12-2x) | | 4(x+1)+5=2x+2(4+x) | | 2.67x+1.167-3.4x=5.2 | | -7+2x=5(x-2) | | 15a-7x=-30 | | y^2+y-14520=0 | | 0.12x=0.432 | | 6r-1+6+3=17 | | (5y+9)(8-y)=0 | | 8x+7=6-2-10x | | 3(3n-5)=(7n+4)+1 | | -3x-3(x+1)=39 | | 40m^3-320m^2-56m+488=0 | | (8x-8y)=-24 | | -50+3*x=-11 | | 0.375x+1.167x=5.2 | | y+2r=5 | | 7p-(3p+4)=2(2p-1) | | 7x+15=5x+12 | | (-2z-7)(-8z+5)=0 | | 6x-9=6(x+3) | | y=4x^8-4x^6 | | (-2z-7)(-8+5)=0 | | X-14=-36 | | 25y-36y^2= | | 27x-6+15x^2= | | (x-7)(-4x+5)=0 | | -28-4v=-2v+8(v-6) | | 7x-17+3x+117=180 | | (w-7)(-6w+5)=0 | | 3x^3-24x^2-3x+24=0 | | 5(6x+3)=10(3x-4) |